Mitochondrial genome sequence of tuber-bearing wild potato, Solanum commersonii Dunal. Issue 1 (2nd January 2018) - Cho, Kwang-Soo; Cho, Ji-Hong; Im, Ju-Sung; Choi, Jang-Gyu; Park, Young-Eun; Hong, Su-Young; Park, Tae-Ho
Abstract: We report two complete mitochondrial genome sequences of a tuber-bearing wild potato species ( Solanum commersonii ). The genomes are circular DNA molecules with lengths of 213, 676 bp and 338, 427 bp containing 80 nonredundant genes totally, including 34 protein-coding genes, 25 hypothetical open reading frames, 18 tRNA genes, and 3 rRNA genes. Phylogenetic analysis using common protein-coding sequences confirmed that S. commersonii belongs to the Solanoideae subfamily in the Solanaceae family.